Why did the Soviet Union lose the manned race to the Moon? - Silva Betzler, Alberto (Cadernos de Astronomia, 2024)
Almost seventy years ago, after the launch of Sputnik-1 and the beginning of a series of satellites with a mass in the order of tons, the Union of Soviet Socialist Republics (USSR) demonstrated that it had rockets with a larger payload capacity than their counterparts elsewhere in the world. This was the result of a highly developed program based on an efficient space research and development network. This suggested that the next natural step was the conquest of the moon and the other planets of the solar system. Less than ten years later, however, the Soviet and American programs were on a completely different level: cosmonaut Komarov had died in the first Soyuz-1 flight test and Apollo–8 undertook the first manned orbit of the moon. After the first American moon landing in July 1969, Soviet officials announced to the world that there had never been a program aimed at landing cosmonauts on the lunar surface. With the end of the USSR in 1991, secret documents on the subject were published, revealing the opposite. The reasons for the USSR's lack of success in landing cosmonauts on the lunar surface are complex and varied and are analyzed in this article.
Keywords: astronautics; Soviet Union; space race